2014
DOI: 10.1016/j.bbi.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Divergent gene expression responses to Complicated Grief and Non-complicated Grief

Abstract: The “widowhood effect” (i.e., morbidity/mortality in recently bereaved spouses) may be related to changes in immune function, but little is known about the impact of bereavement on gene transcription in immune cells. This study examined how Complicated Grief and Non-complicated Grief responses to bereavement differentially affect leukocyte gene expression. Genome-wide transcriptional profiling and bioinformatic analyses were completed on 63 older adults. Thirty-six of them had lost their spouse/partner on aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Still, bereavement is associated with a variety of negative mental and physical health outcomes (for reviews: Stroebe, Schut, & Stroebe, ; Zisook et al, ). Physical health outcomes include an increased risk of mortality (Buckley et al, ), suicidality (Prigerson et al, ; Zisook et al, ), and morbidity (Buckley et al, ; Keyes et al, ; O'Connor, Schultze‐Florey, Irwin, Arevalo, & Cole, ). Mental health outcomes include depression, post‐traumatic stress disorder (PTSD), and difficulties in grieving that extend in duration and severity beyond the scope of “normal” grief symptoms, also termed complicated grief (CG) (Zisook et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Still, bereavement is associated with a variety of negative mental and physical health outcomes (for reviews: Stroebe, Schut, & Stroebe, ; Zisook et al, ). Physical health outcomes include an increased risk of mortality (Buckley et al, ), suicidality (Prigerson et al, ; Zisook et al, ), and morbidity (Buckley et al, ; Keyes et al, ; O'Connor, Schultze‐Florey, Irwin, Arevalo, & Cole, ). Mental health outcomes include depression, post‐traumatic stress disorder (PTSD), and difficulties in grieving that extend in duration and severity beyond the scope of “normal” grief symptoms, also termed complicated grief (CG) (Zisook et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bereavement is a significant modulator of immune cell gene expression, genes involved in innate antiviral responses. 9 The downregulation of these genes is consistent with increased vulnerability to infectious diseases in bereaved older adults where this body of research has been concentrated. The presence of altered physiology could further increase health risk.…”
Section: Discussionmentioning
confidence: 88%
“…36 Similarly, in another work the authors found that spouses suffering complicated grief in response to bereavement presented a marked down-regulation of type I IFN-related transcripts compared to spouses with no complicated grief. 18 In addition, a recent study showed that a yogic meditation intervention could reverse the pattern of increased NF-jB-related transcription of pro-inflammatory cytokines and decreased IRF1-related transcription of the innate antiviral response in healthy individuals under a significant life stressor. 37 The decreased interferon response in subjects with low scores of SRH may have clinical implications for the resistance to infectious disease.…”
Section: Discussionmentioning
confidence: 99%